2014
DOI: 10.1161/circheartfailure.113.000697
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Cardiac Troponin I Assay to Screen for Acute Rejection in Patients With Heart Transplant

Abstract: Background— A noninvasive biomarker that could accurately diagnose acute rejection (AR) in heart transplant recipients could obviate the need for surveillance endomyocardial biopsies. We assessed the performance metrics of a novel high-sensitivity cardiac troponin I (cTnI) assay for this purpose. Methods and Results— Stored serum samples were retrospectively matched to endomyocardial biopsies in 98 cardiac transplant recipients, who survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…These cardiac biomarkers for injury represented in Table 2 are for autologous hearts. A high-sensitivity troponin has been retrospectively correlated to biopsy-based acute rejection events in heart transplants (21). The biological variability was not computed, but the range of troponin from a reference population (n = 88) with no history of acute rejection was relatively wide: the median troponin was 9.45 ng/L, the 60th percentile was 15 ng/L, and 10 outliers that ranged from 60.9 to 268 ng/L were excluded from the main data analyses (21).…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…These cardiac biomarkers for injury represented in Table 2 are for autologous hearts. A high-sensitivity troponin has been retrospectively correlated to biopsy-based acute rejection events in heart transplants (21). The biological variability was not computed, but the range of troponin from a reference population (n = 88) with no history of acute rejection was relatively wide: the median troponin was 9.45 ng/L, the 60th percentile was 15 ng/L, and 10 outliers that ranged from 60.9 to 268 ng/L were excluded from the main data analyses (21).…”
Section: Articlesmentioning
confidence: 99%
“…A high-sensitivity troponin has been retrospectively correlated to biopsy-based acute rejection events in heart transplants (21). The biological variability was not computed, but the range of troponin from a reference population (n = 88) with no history of acute rejection was relatively wide: the median troponin was 9.45 ng/L, the 60th percentile was 15 ng/L, and 10 outliers that ranged from 60.9 to 268 ng/L were excluded from the main data analyses (21). In contrast, our current study of a renal transplant reference population indicated that ddcfDNA has a narrower range between its median of 0.21% and 96th percentile cutoff of 1%, and we did not exclude outliers.…”
Section: Articlesmentioning
confidence: 99%
“…While impractical in the general population, a number of settings may warrant repeat cTn testing. As the rise in cTn has been shown to predict rejection of a transplanted heart, serial cTn testing might be warranted in transplant recipients [109]. Similarly, patients who are about to undergo potentially cardiotoxic therapy may benefit from serial cTn testing and a switch to a different therapy when a predetermined allowable increase in cTn is exceeded [32].…”
Section: Additional Considerations In Predicting Adverse Eventsmentioning
confidence: 99%
“…HscTnT and hscTnI have been evaluated in retrospective studies and found useful in surveillance of cardiac sarcoidosis activity and a biomarker for ruling out acute rejection in cardiac transplant recipients. 27,28 In this study, we used hscTnT as a biomarker for subclinical myocardial injury to determine whether 6 months of treatment with rosiglitazone causes an increase in levels when compared to a placebo. We observed that despite an increase in hscTnT levels from baseline to follow-up, there was no difference between the rosiglitazone and placebo group, suggesting that use of rosiglitazone is not associated with any significant increase in myocardial injury.…”
Section: Discussionmentioning
confidence: 99%